Application of the NetLogo Tool in Ischemic Stroke Simulation - de Aguiar, Paulo Victor; de Sá, Claudio Cesar; de Lima, Helder Geovane Gomes; Amaral, Augusto Radünz; Parpinelli, Rafael Stubs (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2018: Anais do XV Encontro Nacional de Inteligência Artificial e Computacional, 2018)
This paper presents the proposal of a mathematical model for ischemic stroke, which is implemented with multiagent systems, in a general purpose tool known as NetLogo. The objective of this simulator is to obtain a partial view of the stroke for didactic purposes and to motivate future works for the treatment of the disease. Given the importance of stroke, we want to know how it evolves after its initial symptom, over time. This simulator allows a study of the evolution of the disease, regarding the speed of growth and the affected areas in certain region of the brain.